Fever with pancytopenia: unusual presentation of extrapulmonary tuberculosis: a case report - Chamara Dalugama; Indika Bandara Gawarammana (Journal of Medical Case Reports, 2018)
Abstract Background Tuberculosis is a major health problem in the developing world. Diagnosis of extrapulmonary tuberculosis is delayed because the presentation is nonspecific. Extrapulmonary tuberculosis can present with various hematological manifestations, including pancytopenia. Pancytopenia could be due to hypersplenism, maturation arrest, hemophagocytic lymphohistiocytosis, or infiltration of the bone marrow by caseating or noncaseating granulomas causing reversible or irreversible fibrosis. Case presentation We report a case of a 56-year-old Sri Lankan Sinhalese man who presented with pyrexia of known origin with significant loss of weight and loss of appetite. He had mild pallor with mild hepatosplenomegaly. He had high inflammatory markers with pancytopenia in a peripheral blood smear. His chest radiograph was unremarkable, and he had a negative Mantoux test result. A diagnosis of disseminated tuberculosis was made on the basis of caseating tuberculous granulomas in the bone marrow. Conclusions Disseminated tuberculosis remains a diagnostic challenge because the presentation is vague and nonspecific. In case of pyrexia of unknown origin with peripheral cytopenia, the possibility of disseminated tuberculosis should be considered, particularly in endemic areas. Simultaneous culture and histopathological examination of the bone marrow is important in such instances, because results of common tests such as chest radiography or Mantoux tests can be negative.